Managing Neglected Burn Wound with Exposed Upper Tibia Using Multiple Modalities - Kalangi, Cherry G; Hariyanto, Agus; Oley, Mendy Hatibie (Lingkar Studi Bedah Plastik Foundation, 2013)
Background: Deep burn wound with exposed underlying structures such as muscle or moreover in this case, bone, may increase morbidity in the terms of infection. Therefore careful planning of reconstruction is needed. Patient and Method: We report one case of neglected burn wound with exposed tibia and muscle contracture on bilateral knee joint that was reconstructed in our Plastic Surgery Division of Prof RD Kandou Hospital. Data was taken from medical and surgery record. Result: We managed the muscle contracture of the left knee joint by sedated gradual stretching and splinting. We also utilized hyperbaric treatment in order to maximize granulation process. A medial gastrocnemius muscle flap followed by split thickness skin graft is used to reconstruct the missing tissue at upper tibia, and another split thickness skin graft to cover another wound at opposite upper leg. The result was satisfying without any complication. Conclusion: In managing a neglected burn wound with bone exposed and muscle contracture, it is compulsory to have a careful reconstruction planning. Our objectives are to release the muscle contracture and to provide an adequate coverage to the bone-exposed wound by using many modalities we have.